Return of 4U 1730–22 after 49 yr Silence: The Peculiar Burst Properties of the 2021/2022 Outbursts Observed by Insight-HXMT - Chen, Yu-Peng; Zhang, Shu; Ji, Long; Zhang, Shuang-Nan; Wang, Peng-Ju; Kong, Ling-Da; Chang, Zhi; Peng, Jing-Qiang; Shui, Qing-Cang; Li, Jian; Li, Zhao-Sheng; Tao, Lian; et al. (The Astrophysical journal, 2023)
Staying in quiescence for 49 yr, 4U 1730–22 became active and had two outbursts in 2021 and 2022; 10 thermonuclear X-ray bursts were detected with Insight-HXMT. Among them, the faintest burst showed a double-peaked profile, placing the source as the seventh accreting neutron star (NS) exhibiting double-peaked type I X-ray bursts; the other bursts showed photospheric radius expansion (PRE). The properties of a double-peaked non-PRE burst indicate that it could be related to a stalled burning front. For the five bright PRE bursts, apart from the emission from the neutron star (NS) surface, we find the residuals both in the soft (<3 keV) and hard (>10 keV) X-ray bands. Time-resolved spectroscopy reveals that the excess can be attributed to an enhanced preburst/persistent emission or the Comptonization of the burst emission by the corona. We find, the burst emission shows a rise until the photosphere touches down to the NS surface rather than the theoretical predicted constant Eddington luminosity. The shortage of the burst emission in the early rising phase is beyond the occlusion by the disk. We speculate that the findings above are due to that the obscured part (not only the lower part) of the NS surface is exposed to the line of sight due to the evaporation of the obscured material by the burst emission, or the burst emission is anisotropic ( ξ > 1) in the burst early phase. In addition, based on the fluxes of PRE bursts at their touchdown times, we derive a distance estimation as 9.0–12.4 kpc.